Pemikiran Pendidikan Menurut KH Abdul Wahid Hasyim - Ana Rodhiyatus Sholikhah; Muqowim Muqowim (LPPM IAINU Kebumen, 2022)
Internal challenges and external challenges in the development of the Islamic education curriculum are the background to the importance of conducting a study of KH. Abdul Wahid Hasyim about education. This library research study seeks to answer the question of the implications of Islamic education based on the study of KH. Abdul Wahid Hasyim with the Islamic education curriculum in Indonesia today? Through content analysis and exploration, a discussion was produced that the implications of Islamic education based on the study of KH. Abdul Wahid Hasyim on the Islamic education curriculum in Indonesia, which includes curriculum coverage, principles, characteristics or characteristics, and principles of the Islamic education curriculum. These four implications are expected to have a positive impact on the development of the Islamic education curriculum in Indonesia in a better direction.